Hydrodynamic Analysis of Partially Filled Liquid Tanks Subject to 3D Vehicular Manoeuvring - Mengmeng Han; Jian Dai; C. M. Wang; K. K. Ang (Shock and Vibration)
This paper is concerned with liquid sloshing in a partially filled container due to 3-dimensional vehicle motion. The liquid sloshing is described by a set of linear modal equations derived from the potential flow theory, which can be applied to liquid sloshing induced by arbitrary combination of lateral, longitudinal, and rotational excitations. The sloshing force and moment are expressed with a set of hydrodynamic coefficients that are determined by the linear velocity potential. These coefficients can be precalculated and incorporated into the motion equations of the vehicle system so that a fully coupled vehicle-sloshing model is available. In addition, we propose an approach to calculate the hydrodynamic coefficients using the outputs of commercial frequency-domain boundary element software in order to maximize the efficiency of modelling and computation. The accuracy of the proposed model is examined by comparison with available CFD and model test data in the literature. The case of a road tanker encountering a road bump during acceleration/braking is investigated. Results show that the tank rotational motion will affect the amplitude and the sloshing force, and neglecting tank rotation may lead to underestimation of the sloshing force magnitude.